A potential of iron slag-based soil amendment as a suppressor of greenhouse gas (CH4 and N2O) emissions in rice paddy - Galgo, Snowie Jane C.; Canatoy, Ronley C.; Lim, Ji Yeon; Park, Hyon Chol; Kim, Pil Joo (Frontiers in Environmental Science, 2024)
Iron slag-based silicate fertilizer (SF) as a soil amendment has been utilized for over 50 years in rice paddy. SF which contains electron acceptors such as oxidized iron (Fe3+) compounds was known to reduce methane (CH4) emission, with a global warming potential (GWP) of 23 higher than carbon dioxide (CO2). However, it was questionable to the dynamics of nitrous oxide (N2O) with a GWP of 265. Since the reduced Fe (Fe2+) can react as an electron donor, SF application might suppress N2O emission by progressing N2O into nitrogen gas (N2) during the denitrification process. To verify the influence of SF application on two major greenhouse gas (GHG) dynamics during rice cultivation, three different kinds of SF were prepared by mixing iron rust (>99%, Fe2O3) as an electron acceptor with different ratios (0, 2.5, and 5%) and applied with the recommended level (1.5 Mg ha-1) for rice cultivation. SF application was effective to decrease CH4 emission in the earlier rice cropping season, and seasonal CH4 flux was more highly decreased with increasing the mixing ratio of iron rust from an average of 19-38%. Different from CH4 emission, approximately 70% of seasonal N2O flux was released after drainage for rice harvesting. However, SF incorporation was very effective to decrease N2O emission by around 40% over the control. The reduced Fe2+ can be simultaneously oxidized into Fe3+ by releasing free electrons. The increased electron availability might develop more denitrification processes into N2 gas, rather than NO and N2O, and then decrease N2O emission in the late rice cultivation season. We could find evidence of a more suppressed N2O flux by applying the electron acceptor added SFs (SF2.5 and SF5.0) to 49-56% decreased over the control. SF application was effective to increase rice productivity which was negative-quadratically responded to available silicate (SiO2) concentration in soil at the harvesting stage. Grain yield was maximized at around 183 mg kg-1 of available SiO2 concentration with a 16% increase over no-SF application. Consequently, SF has an attractive potential as a soil amendment in rice paddy to decrease GHG emission impacts, as well as to increase rice productivity.